Effect of Ag Nanoparticles Addition on the Microstructure of Cu-21%Zn-6%Al Shape Memory Alloys - Alhassan, Zainab Salim Abd; Jabbar, Murtadha Abbas (Basrah Journal for Engineering Sciences, 2021)
This paper aims to investigate the effect of Ag nanoparticles addition in different percentages (0.12 wt. %, 0.15 wt. %, 0.25 wt. %, 0.35 wt. %) on the microstructure properties of Cu-21%Zn-6%Al shape memory alloy. Optical and SEM were carried out to studied such effects. Two heat treatments were carried out at (825 ℃ and 850 ℃) for 10 min and quenched in ice water. It was observed that both of heat treatment lead to formation M18R martensite with V-shape and needle like, but raising the temperature of heat treatment from 825 ℃ to 850 ℃ lead to a decrease formation α phase, which leads to improving the shape memory properties. Refinement of the grain size resulted as Ag nanoparticles addition increased from 0 to 0.25 wt. %, the grain size decreases from 1551 μm to 212 μm with reduction of 86.32 wt. % at 0.25 wt. % Ag. The microstructure observation indicated that the Ag nanoparticles addition leads to creating a multi-variant oriented martensite microstructure after quenching process in ice water.